DEVELOPMENT OF COMMUNICATIVE AND INTERCULTURAL COMPETENCIES IN ENGLISH TEACHING THROUGH THE USE OF INTERNET RESOURCES - Mansurova, Shohista (Журнал иностранных языков и лингвистики, 2023)
In our article, issues related to the development of communicative and intercultural competencies in teaching English through the use of INTERNET resources are discussed and considered